Effect of age on the median effective dose and 95% effective dose of intravenous fentanyl for blunting the hemodynamic response to tracheal intubation: A double-blind, up-and-down sequential method trial - Jatuporn Eiamcharoenwit; Phuping Akavipat (Journal of Anaesthesiology Clinical Pharmacology)
Background and Aims: Control of the hemodynamic response during intubation is essential. To assess the effect of age on the median effective dose (ED50) and 95% effective dose (ED95) of fentanyl for blunting the hemodynamic response to intubation. Material and Methods: Patients (n = 86) undergoing general anesthesia were randomly stratified according to age (groups 1–4); fentanyl was administered to each patient according to the Dixon and Massey method, starting at 2 μg/kg. The dose was increased or decreased by 0.5 μg/kg for the subsequent patient, depending on the failure or success of blunting of the hemodynamic response, respectively. Success was defined as a change in heart rate and blood pressure by <20% below the baseline at 1, 3, and 5 min after intubation. ED50 and ED95 were analyzed using R statistical software. Results: ED50s of fentanyl in groups 1 (20–35 years), 2 (36–50 years), 3 (51–65 years), and 4 (66–80 years) were 2 μg/kg (90% confidence interval, 1.50–2.50), 2.25 μg/kg (2.00–2.50), 1.89 μg/kg (1.54–2.21), and 1.27 μg/kg (0.72–1.82), respectively. ED95s in groups 1, 2, 3, and 4 were 2.45 μg/kg (2.32–2.96), 2.79 μg/kg (2.58–4.38), 2.44 μg/kg (2.33–3.06), and 2.70 μg/kg (2.30–5.18), respectively. There was a statistically significant incidence of cough in group 2. Conclusions: Patients aged 65–80 years required the lowest ED50 of fentanyl dose, whereas patients aged 36–50 years required the highest ED50 and ED95 dose to blunt the hemodynamic response during intubation.